Psychotic temptation - Abensour, Liliane. (New library of psychoanalysis (Unnumbered), 2013)
"How can we understand the pull towards that which we fear: psychosis? In this thought provoking book, Abensour proposes the idea of a temptation towards psychosis rather than a regression, as a response to the hatred or denial of the subject's origins. She shares her reflections on her psychoanalytic work with psychotic patients focusing on their struggle to achieve a coherent sense of a self that can inhabit a shared world. Abensour locates this struggle within the universal human struggle to achieve a balance between what we can and cannot allow ourselves to know about the reality of death and of our insignificance in the world"--